Analog synthesis of DAMASCENOLIDETM, an important aroma component of roses, and their odor properties. Issue 8 (2nd August 2020) - Miyazawa, Yamato; Kawaguchi, Kenji; Katsuta, Ryo; Nukada, Tomoo; Ishigami, Ken
ABSTRACT: DAMASCENOLIDE TM [1, 4-(4-methylpent-3-en-1-yl)furan-2(5 H )-one], which has a citrus-like odor, is an important aroma component of roses. We have previously reported on the synthesis and odor evaluation of double-bond isomers of 1 and concluded that the position and the geometric isomerism of the double-bond had a significant effect on the odor. For the purpose of deepening knowledge about structure–odor relationships, we synthesized 13 analogs of compound 1 and evaluated their odors. As a result, it was found that the presence of two double-bonds and branched methyl group at the terminal position in the side chain was essential in order to have a citrus-like odor. Substitution of the side chain with appropriate length at the appropriate 4-position of the 2(5 H )-furanone ring was also an important factor in determining the quality of the odor. Graphical abstract: uf0001 Synthesis and odor evaluation of 13 analogs of DAMASCENOLIDE TM were achieved.